HUMAN RELATIONS AND ORGANIZATIONAL CULTURE IN STRATEGIC MANAGEMENT A SOCIO-HUMANISTIC PERSPECTIVE ON MCGREGOR’S AND OUCHI’S THEORIES - Mechri Safi,; Kamel Aouissi, (International Journal of Innovative Technologies in Social Science, 2025)
This paper explores the strategic dimensions of human relations and organizational culture through a socio-humanistic lens. It draws on the theoretical contributions of Douglas McGregor (Theory X and Theory Y) and William Ouchi (Theory Z) to analyze how managerial assumptions about human nature influence leadership styles and organizational dynamics. The study highlights how trust, participation, shared responsibility, and cultural sensitivity serve as essential pillars of effective strategic management. By integrating sociological and organizational insights, this paper argues for a human-centered approach to management that enhances both institutional performance and employee development. The findings emphasize the relevance of these classical theories in addressing contemporary organizational challenges shaped by complexity, cultural diversity, and digital transformation.